Negative plate and lithium ion secondary battery
By using double -layer coating technology on the negative chip of lithium -ion batteries, using silicon oxygen and silicon carbon materials, the problem of polarization and dynamic performance of the volume expansion of silicon negative materials and decline in dynamic performance, and achieve high energy density. , The effect of fast charging and good circulation stability.
Patent Information
- Application Number
- CN202411373973.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
AI Technical Summary
During the charging and discharging process, existing lithium-ion batteries have increased polarization and decreased kinetic performance due to volume expansion of silicon negative electrode material, and have poor cycle life and fast charging performance.
Using dual -layer coating technology, the surface layer of the negative chip is used to use silicon oxygen materials with excellent dynamic properties, and uses high gram capacity and structural stability but weak dynamic performance at the bottom layer. Optimize polarization distribution to the quality ratio of element O.
A significant reduction of negative polarization has improved the dynamic performance and cycle stability of the battery, while taking into account high energy density and fast charging capabilities.
Smart Images

Figure CN119340344A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a lithium ion secondary battery comprising the negative electrode sheet. Background Art
[0002] Lithium-ion batteries have been widely used in mobile phones, laptops, power tools, new energy vehicles, energy storage and other fields due to their advantages such as high energy density and long cycle life. According to market research, range anxiety and charging speed issues have greatly affected the user experience of new energy vehicles, which shows that power batteries are in urgent need of targeted technological innovation. Therefore, power batteries that take into account both high energy density and fast charging performance have become a key research direction.
[0003] Silicon negative electrode material has an ultra-high theoretical specific capacity (4200mAh / g), and has become an important negative electrode material for improving the energy density of lithium batteries. However, due to its special alloying lithium insertion mechanism, its volume expands greatly during battery charging (up to about 300%). The higher volume expansion leads to increased polarization of the negative electrode and decreased kinetic performance during charging and discharging; and the repeated expansion and contraction of silicon negative electrode materials will also cause particle breakage and pulverization, leading to material failure; it is also not conducive to maintaining the integrity of the SEI film, causing continuous side reactions at the negative electrode interface to consume electrolyte, which not only reduces the initial coulomb efficiency, but also affects the cycle life of the battery. At the same time, a higher negative electrode expansion rate is not conducive to maintaining the structural stability of the battery. Excessive internal expansion can easily cause the battery to swell and deform, leading to battery failure. Summary of the invention
[0004] The purpose of the present invention is to overcome the above problems existing in the prior art, and provide a negative electrode sheet and a lithium ion secondary battery including the negative electrode sheet. The lithium ion secondary battery (hereinafter referred to as the battery) including the negative electrode sheet of the present invention can take into account high energy density, fast charging capability and better cycle stability.
[0005] The inventors of the present invention have found that it is precisely because the components of the single-layer structure are uniform that the infiltration effect of the electrolyte from the bottom layer to the surface layer of the pole piece and the current density distribution are uneven, resulting in polarization inside the pole piece, and the surface polarization is larger and the bottom layer polarization is smaller. This uneven polarization will be more obvious when the charge and discharge current increases, resulting in the preferential deintercalation of lithium by the surface active material in the pole piece, and the deintercalation of lithium by the bottom active material is more delayed. Silicon oxygen materials have more excellent kinetic properties and are suitable for being placed on the surface layer to enable them to quickly realize lithium ion deintercalation, while silicon carbon materials have higher gram capacity and structural stability, but their kinetic properties are insufficient. They are suitable for being placed on the bottom layer so that they can slowly accept lithium ions and give full play to their high capacity advantages. At this time, the overall polarization of the negative electrode sheet can be reduced. For the negative electrode, excessive polarization will affect the kinetic properties of the negative electrode sheet, causing lithium precipitation when the charging rate increases, thereby affecting the cycle life and fast charging performance of the battery. Therefore, the inventors of the present invention adopted a multi-layer coating technology for negative electrode sheets (such as a double-layer coating technology), and according to the polarization law of the surface and bottom layers in the negative electrode sheets, used different and specific active materials in different coatings to solve the problem of excessive polarization of the negative electrode.
[0006] Taking into account the adverse effects of the volume expansion of silicon negative electrode materials on the battery and the polarization law of the surface and bottom layers in the negative electrode sheet, the inventors of the present invention found that silicon-oxygen materials can be arranged on the surface of the negative electrode sheet away from the current collector, and silicon-carbon materials can be arranged on the surface of the negative electrode sheet close to the current collector, and by limiting the mass ratio of the element Si to the element O, the battery can have both high energy density and good fast charging performance. The reason is:
[0007] First, silicon-oxygen materials are incomplete oxides of silicon, and their specific capacity (about 1300 mAh / g) is lower than that of silicon-carbon materials; and because silicon-oxygen materials themselves lack constraints on the volume expansion of silicon, their volume expansion rate is larger than that of silicon-carbon materials. However, since silicon-oxygen materials contain a certain amount of element O, an appropriate amount of element O is beneficial to improving the electronic conductivity of the material during the lithium insertion process of silicon-oxygen materials, thereby promoting charge transfer reactions, and the improvement of electronic conductivity helps to increase the diffusion rate of lithium ions. Therefore, both electrons and lithium ions have faster diffusion rates in silicon-oxygen materials, giving the battery more excellent kinetic performance.
[0008] Second, silicon-carbon materials are generally formed by depositing nano-silicon in a carbon skeleton, and their specific capacity (about 1700mAh / g) is higher than that of silicon-oxygen materials; and the coating layer on the outer surface of the silicon-carbon material and its carbon skeleton have a certain inhibitory effect on the volume expansion of silicon, and the carbon skeleton can also provide a certain buffer space for the expansion of silicon. Therefore, the volume expansion of silicon-carbon materials is lower than that of silicon-oxygen materials. However, since the carbon skeleton of the silicon-carbon material itself has a low electronic conductivity, and its barrier effect on the electrolyte will cause a greater lithium ion diffusion impedance, the electron and ion transmission rate of the silicon-carbon material is slower than that of the silicon-oxygen material, lithium precipitation is prone to occur during fast charging, and the temperature rise is also higher.
[0009] In summary, adding silicon to the negative electrode is an effective means to improve the energy density of the battery. In addition, considering the respective characteristics of silicon-carbon materials and silicon-oxygen materials, and combining the polarization laws of the surface and bottom layers of the negative electrode sheet, the silicon-oxygen material with excellent kinetic characteristics is placed on the surface layer of the negative electrode sheet, and the silicon-carbon material with slightly worse kinetic performance but higher gram capacity and higher structural stability is placed on the bottom layer of the negative electrode sheet. During fast charging, the silicon-oxygen material on the surface can exert its kinetic advantages to quickly insert lithium, and then conduct lithium ions to the bottom layer. The silicon-carbon material on the bottom layer can continue to exert its high gram capacity advantage, and the silicon-carbon material has a stable structure and can maintain good adhesion with the negative electrode current collector. The above conditions can achieve complementary advantages, give full play to the kinetic advantages of silicon-oxygen materials and the cyclic stability advantages of silicon-carbon materials, and thus improve the kinetic performance, cyclic performance and energy density of the negative electrode sheet. Based on this, the inventors of the present invention proposed the following scheme:
[0010] A first aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer is away from the negative electrode current collector, and the second negative electrode active material layer is close to the negative electrode current collector; the first negative electrode active material layer comprises a silicon-oxygen material, the silicon-oxygen material comprises element Si and element O, and in the silicon-oxygen material, the mass ratio of element Si to element O is m1; the second negative electrode active material layer comprises a silicon-carbon material, the silicon-carbon material comprises element Si, element C and element O, and in the silicon-carbon material, the mass ratio of element Si to element O is m2; m1 <m2。
[0011] A second aspect of the present invention provides a lithium ion secondary battery, wherein the lithium ion secondary battery comprises the negative electrode sheet described in the first aspect of the present invention.
[0012] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0013] (1) Compared with a single layer, the double-layer coated negative electrode of the present invention can significantly reduce polarization and improve the dynamic performance of the battery;
[0014] (2) The double-layer silicon-doped negative electrode of the present invention has good cycle stability while ensuring a high energy density, and can maintain a low volume expansion during the battery charge and discharge cycle;
[0015] (3) The battery of the present invention can take into account both high energy density and good fast charging capability, and has good cycle stability and cycle expansion.
[0016] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Shown is a schematic structural diagram of the negative electrode sheet of the present invention.
[0018] Figure 2 Shown is a SEM image of a negative electrode sheet according to an embodiment of the present invention. DETAILED DESCRIPTION
[0019] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0020] A first aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer is away from the negative electrode current collector, and the second negative electrode active material layer is close to the negative electrode current collector; the first negative electrode active material layer comprises a silicon-oxygen material, the silicon-oxygen material comprises element Si and element O, and in the silicon-oxygen material, the mass ratio of element Si to element O is m1; the second negative electrode active material layer comprises a silicon-carbon material, the silicon-carbon material comprises element Si, element C and element O, and in the silicon-carbon material, the mass ratio of element Si to element O is m2; m1 <m2。
[0021] like Figure 1 and Figure 2As shown, the negative electrode sheet includes a negative electrode collector 1 and a negative electrode active material layer 2 located on at least one side of the negative electrode collector 1; the negative electrode active material layer 2 includes a first negative electrode active material layer 21 and a second negative electrode active material layer 22 stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer 21 is away from the negative electrode collector, and the second negative electrode active material layer 22 is close to the negative electrode collector. The first negative electrode active material layer 21 includes a silicon-oxygen material 211, and the second negative electrode active material layer 22 includes a silicon-carbon material 221.
[0022] The silicon-carbon material may include element Si, element C and element O. Element O may be introduced during the preparation of the silicon-carbon material.
[0023] In the present invention, the mass ratio of element Si to element O can be obtained by energy dispersive spectrometer (EDS) testing. For example, 5 silicon-oxygen materials are randomly selected in the first negative electrode active material layer, the mass ratio of element Si to element O is tested, and the average value of the mass ratio of element Si to element O in the 5 silicon-oxygen materials is calculated as m1, and 5 silicon-carbon materials are randomly selected in the second negative electrode active material, the mass ratio of element Si to element O is tested, and the average value of the mass ratio of element Si to element O in the 5 silicon-carbon materials is calculated as m2.
[0024] The present invention arranges a first negative electrode active material layer including silicon oxide material away from the negative electrode current collector (that is, the first negative electrode active material layer including silicon oxide material is located at the surface layer), so that the silicon oxide material located at the surface layer can take advantage of the faster diffusion speed of electrons and lithium ions in the silicon oxide material, preferentially deintercalate lithium during high-rate charging, and transfer lithium ions to the bottom layer in time; arranges a second negative electrode active material layer including silicon carbon material close to the negative electrode current collector (that is, the second negative electrode active material layer including silicon carbon material is located at the bottom layer), so that the silicon carbon material located at the bottom layer can take advantage of its higher specific capacity, lower expansion, and better cycle, provide more lithium insertion sites during the charging process, and reduce the overall expansion of the negative electrode sheet, so as to improve the overall cycle stability of the negative electrode sheet; and both silicon oxide material and silicon carbon material can increase the overall specific capacity of the negative electrode sheet, so as to improve the energy density of the battery. At the same time, by controlling the mass ratio of the element Si and the element O of the silicon-oxygen material in the first negative electrode active material layer to be less than the mass ratio of the element Si and the element O of the silicon-carbon material in the second negative electrode active material layer, the oxygen element distribution in the surface layer of the negative electrode sheet is made higher than the oxygen element distribution in the bottom layer, thereby improving the electron and lithium ion transmission rate of the surface layer, so that the battery has more excellent kinetic performance, and the higher electron and lithium ion transmission rate of the surface layer can make the electrons and lithium ions transfer to the bottom layer more quickly, so that the overall current density distribution of the negative electrode sheet is more uniform, avoiding the occurrence of polarization phenomenon inside the electrode sheet, and at the same time, it can also keep the silicon-carbon material in the bottom layer at a higher gram capacity, thereby improving the overall energy density of the battery, so that the battery can take into account both good fast charging performance and cycle stability, and has a lower cycle expansion rate.
[0025] In the present invention, by arranging silicon-oxygen material on the surface of the negative electrode sheet away from the current collector, arranging silicon-carbon material on the surface of the negative electrode sheet close to the current collector, and controlling the mass ratio of element Si and element O in the two, compared with the prior art, the battery can have both good first coulomb efficiency and cycle stability, and has a lower cycle expansion rate. In order to further improve the effect, one or more of the technical features can be further optimized.
[0026] In one example, m1 / m2 is 0.001-0.12 (eg, 0.001, 0.002, 0.005, 0.008, 0.1, or 0.12).
[0027] In one example, m1 / m2 is 0.0023-0.05.
[0028] In one example, m1 is 0.8-1.2. The mass ratio of element Si to element O in the silicon oxide material in the surface layer is controlled within the above range. The optimized Si / O ratio can promote the transmission of ions and electrons in the silicon oxide material and inhibit the particle expansion of the silicon oxide material during the charge and discharge process.
[0029] In one example, m1 is 0.9-1.
[0030] In one example, m2 is 7.5-500. Controlling the mass ratio of element Si to element O in the silicon-carbon material in the bottom layer within the above range can make the silicon-carbon material have a higher gram capacity, which is beneficial to improving the energy density of the battery.
[0031] In one example, m2 is 20-400.
[0032] In one example, m1 / m2 is 0.0023-0.05, m1 is 0.9-1, and m2 is 20-400.
[0033] In one example, when the battery including the negative electrode sheet is in a 0% SOC state, the vertical distance from the surface of the silicon oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d1, and the vertical distance from the surface of the silicon carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d2; d1 is 0μm-35μm (for example, 0μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm or 35μm), and d2 is 0μm-26μm (for example, 0μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm or 26μm).
[0034] Wherein, d1 is the vertical distance from any position on the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the battery including the negative electrode sheet is in the 0% SOC state; d2 is the vertical distance from any position on the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the battery including the negative electrode sheet is in the 0% SOC state.
[0035] In the present invention, d1 and d2 can be obtained by testing by conventional methods in the art, such as using SEM, discharging the battery to a 0% SOC state, taking out the negative electrode sheet, and cutting the negative electrode sheet in the cross-sectional direction, and then observing it under the SEM, measuring the minimum value of the vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer as the "vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer"; and measuring the minimum value of the vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer as the "vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer".
[0036] In one example, d1 is 0 μm-30 μm, and d2 is 0 μm-20 μm.
[0037] In one example, when the battery including the negative electrode sheet is in a 100% SOC state, the vertical distance from the surface of the silicon oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d3, and the vertical distance from the surface of the silicon carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d4; d3 is 0μm-40μm (for example, 0μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm or 40μm), and d4 is 0μm-35μm (for example, 0μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm or 35μm).
[0038] Among them, d3 is the vertical distance from any position on the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the battery including the negative electrode sheet is in a 100% SOC state; d4 is the vertical distance from any position on the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the battery including the negative electrode sheet is in a 100% SOC state.
[0039] In the present invention, d3 and d4 can be obtained by testing by conventional methods in the art, such as using SEM, discharging the battery to 100% SOC state, taking out the negative electrode sheet, and cutting the negative electrode sheet in the cross-sectional direction, and then observing it under SEM, measuring the minimum value of the vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer as the "vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer"; and measuring the minimum value of the vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer as the "vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer".
[0040] When the battery including the negative electrode sheet is in a 0% SOC state, the vertical distance from the surface of the silicon-oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d1, and the vertical distance from the surface of the silicon-carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d2; d1 is 0μm-35μm, and d2 is 0μm-26μm, and / or, when the battery including the negative electrode sheet is in a 100% SOC state, the vertical distance from the surface of the silicon-oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d3, and the vertical distance from the surface of the silicon-carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d4; d3 is 0μm-40μm, and d4 is 0μm-35μm.
[0041] By controlling the vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer and the vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the battery including the negative electrode sheet is in a 0% SOC and / or 100% SOC state, the thickness of the first negative electrode active material layer and the second negative electrode active material layer can be controlled within an appropriate range, thereby ensuring that the kinetically superior silicon-oxygen material in the first negative electrode active material layer (surface layer) is in full contact with the electrolyte and can receive the electrolyte. The second negative electrode active material layer (bottom layer) further receives the lithium ions conducted from the first negative electrode active material layer (surface layer), and increases the overall capacity of the negative electrode with its own larger gram capacity. At this time, the negative electrode polarization will not be large and lithium deposition will not occur due to insufficient contact between the active material and the electrolyte due to the excessive thickness of the negative electrode sheet; nor will the negative electrode surface density be low due to the small thickness of the negative electrode sheet, thereby reducing the battery energy density. Therefore, it can ensure that the battery has the advantages of improved lithium deposition and high energy density.
[0042] In the present invention, "the battery is in a 0% SOC state" means that the battery is discharged to the lower limit voltage [for example, 2.5V for ternary high-nickel materials (the molar content of elemental nickel is 80% and above)); "the battery is in a 100% SOC state" means that the battery is charged to the upper limit voltage [for example, 4.2V for ternary high-nickel materials (the molar content of elemental nickel is 80% and above)].
[0043] In one example, d3 is 0 μm-36 μm, and d4 is 0 μm-30 μm.
[0044] In one example, d3-d1 is 0μm to 40μm, and d4-d2 is 0μm to 35μm. By controlling the difference between d3 and d1 and the difference between d4 and d2, the expansion of the negative electrode during the charge and discharge process can be controlled within a reasonable range, thereby avoiding excessive expansion resulting in a large distance from the negative electrode surface to the current collector, making it difficult for lithium ions to diffuse to the bottom layer of the negative electrode and causing lithium deposition at the negative electrode.
[0045] In one example, d1 is 0 μm-30 μm, d2 is 0 μm-20 μm, d3 is 0 μm-36 μm, and d4 is 0 μm-30 μm.
[0046] In one example, in the silicon-oxygen material, a mass ratio of element Si to element O is 0.8-1.2 (eg, 0.8, 0.85, 0.9, 0.95, 1, or 1.2).
[0047] In one example, the average particle size D1 of the silicon-oxygen material is 5 μm-15 μm (eg, 5 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, or 15 μm).
[0048] In the present invention, the average particle size can be obtained by electron microscopy or laser particle size analyzer. For example, taking the average particle size of silicon oxide material as an example, at least 20 silicon oxide particles are randomly selected within the field of view of the electron microscope by SEM, and the average value is taken to obtain the average particle size of the silicon oxide material.
[0049] In one example, in the silicon-oxygen material, the mass ratio of element Si to element O is 0.8-1.2, and the average particle size D1 of the silicon-oxygen material is 5 μm-15 μm. By controlling the mass ratio of element Si to element O in the silicon-oxygen material within the above range, the expansion of silicon-oxygen particles during lithium insertion and extraction can be suppressed, the rupture of silicon-oxygen particles can be avoided, and the integrity of silicon-oxygen particles can be maintained. At the same time, the relatively low average particle size is conducive to improving the dynamic properties of the silicon-oxygen material.
[0050] In one example, the silicon-oxygen material further includes element Li and / or element Mg. The silicon-oxygen material including element Li and / or element Mg is a silicon-oxygen material that has been chemically pre-lithiated or pre-magnesiated. The silicon-oxygen material treated by this method has active sites on its surface that can chemically react with lithium ions occupied in advance by the pre-lithiation / pre-magnesiation reaction, thereby reducing the side reactions of active lithium on the surface of the silicon-oxygen material located in the surface layer (first negative electrode active material layer), improving the first cycle coulomb efficiency, and increasing the capacity and energy density of the battery.
[0051] In one example, the mass content of element Mg in the silicon-oxygen material is 200ppm-10000ppm. When the mass content of element Mg in the silicon-oxygen material is controlled within the above range, the side reaction of active lithium on the surface of the silicon-oxygen material can be reduced, and the first-cycle coulombic efficiency can be improved.
[0052] In the present invention, the mass content of element Mg in the silicon-oxygen material can be obtained by EDS or ICP testing.
[0053] In one example, the surface of the silicon-oxygen material is coated with a carbon layer formed by a carbon material. The carbon layer is conducive to further promoting the diffusion of lithium ions. For the double-layer coated negative electrode sheet of the present invention, it is conducive to further reducing the polarization of the surface layer and promoting the diffusion of lithium ions into the negative electrode, thereby improving the dynamic performance of the battery.
[0054] In one example, the thickness of the carbon layer on the surface of the silicon-oxygen material is 10 nm to 200 nm (eg, 10 nm, 30 nm, 50 nm, 80 nm, 100 nm, 130 nm, 150 nm, 180 nm, or 200 nm).
[0055] In one example, in the silicon-carbon material, the mass ratio of element Si to element C is 0.82-1.22 (for example, 0.82, 0.85, 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2 or 1.22). In the present invention, the mass ratio of element Si to element C can be obtained by EDS testing. For example, 5 silicon-carbon materials are randomly selected in the second negative electrode active material layer, and the mass ratio of element Si to element C is tested. The average value of the mass ratio of element Si to element C in the 5 silicon-carbon materials is calculated as the mass ratio of element Si to element C.
[0056] In one example, in the silicon-carbon material, the mass ratio of element Si to element C is 0.9-1.1.
[0057] In one example, the silicon-carbon material includes a carbon layer, a carbon skeleton and nano-silicon particles, wherein the nano-silicon particles are deposited in the carbon skeleton and the carbon layer is coated on the surface of the carbon skeleton.
[0058] In one example, an average particle size D3 of the silicon-carbon material is 6 μm-14 μm (eg, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm or 14 μm).
[0059] In one example, in the silicon-carbon material, the mass ratio of element Si to element C is 0.6-1.5, and the average particle size D3 of the silicon-carbon material is 6μm-14μm. Controlling the mass ratio of element Si to element C in the silicon-carbon material within the above range can make the carbon skeleton of the silicon-carbon material well coated, thereby effectively inhibiting the expansion of silicon-carbon particles. At the same time, the relatively low average particle size is conducive to improving the dynamic properties of the silicon-carbon material. It can be understood that element C includes element C in the carbon layer and element C in the carbon skeleton.
[0060] In one example, in the silicon-oxygen material, the mass ratio of element Si to element O is 0.8-1.2, and in the silicon-carbon material, the mass ratio of element Si to element C is 0.9-1.1.
[0061] According to a specific embodiment, the first negative electrode active material layer further includes first carbon-based particles, and the second negative electrode active material layer further includes second carbon-based particles.
[0062] In one example, the average particle size of the silicon-oxygen material is D1, the average particle size of the first carbon-based particles is D2, the average particle size of the silicon-carbon material is D3, and the average particle size of the second carbon-based particles is D4, and D1, D2, D3 and D4 satisfy: D2 / D1 is 1.1-2.3 (for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2 or 2.3), and D4 / D3 is 1.3-2.6 (for example, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5 or 2.6). By controlling the ratio of the average particle size of the first carbon-based particles to the average particle size of the silicon-oxygen material and the ratio of the average particle size of the second carbon-based particles to the average particle size of the silicon-carbon material within the above range, it is possible to achieve size matching between the first carbon-based particles and the silicon-oxygen material and size matching between the second carbon-based particles and the silicon-carbon material, thereby forming a good co-embedded environment, that is, the silicon-oxygen material can be effectively filled in the gaps between the first carbon-based particles, and the silicon-carbon material can be effectively filled in the gaps between the second carbon-based particles, thereby improving space utilization and compaction density. At the same time, during charging, the gaps between the first carbon-based particles can provide a buffer space for the expansion of the silicon-oxygen material, and the gaps between the second carbon-based particles can provide a buffer space for the expansion of the silicon-carbon material, thereby reducing the overall expansion of the negative electrode sheet during the charge and discharge cycle, which is beneficial to maintaining the integrity of the negative electrode interface, thereby improving the battery cycle life.
[0063] In one example, D2 / D1 is 1.5-2, and D4 / D3 is 1.6-2.2.
[0064] In one example, D1 is 5 μm-15 μm, and D2 is 4 μm-22 μm, and D3 is 6 μm-14 μm, and D4 is 8 μm-25 μm.
[0065] In one example, the median particle size Dv50 of the silicon-oxygen material is 7μm-12μm, the median particle size Dv50 of the first carbon-based particles is 10μm-20μm, the median particle size Dv50 of the silicon-carbon material is 6μm-10μm, and the median particle size Dv50 of the first carbon-based particles is 10μm-20μm.
[0066] In the present invention, the median particle size Dv50 can be obtained by testing with a laser particle size analyzer.
[0067] In one example, the silicon-oxygen material is located in gaps formed by a plurality of the first carbon-based particles.
[0068] In one example, the silicon-carbon material is located in gaps formed by a plurality of the second carbon-based particles.
[0069] like Figure 2 As shown, it can be seen that the silicon-oxygen material 211 is located in the gap formed by a number of first carbon-based particles, that is, the silicon-oxygen material is surrounded by the first carbon-based particles. At this time, the gap formed by the number of first carbon-based particles can provide a buffer space for the expansion of the silicon-oxygen material; the silicon-carbon material 221 is located in the gap formed by a number of second carbon-based particles, that is, the silicon-carbon material is surrounded by the first carbon-based particles. At this time, the gap formed by the number of second carbon-based particles can provide a buffer space for the expansion of the silicon-carbon material, and can also improve the space utilization and the compaction density of the negative electrode sheet.
[0070] In one example, the silicon-oxygen material is located in gaps formed by a plurality of the first carbon-based particles, and the silicon-carbon material is located in gaps formed by a plurality of the second carbon-based particles.
[0071] In one example, in the first negative electrode active material layer, based on the total weight of the silicon-oxygen material and the first carbon-based particles, the weight content of the silicon-oxygen material is ≤20 wt %, and the total weight of the first carbon-based particles is ≥80 wt %.
[0072] In one example, in the second negative electrode active material layer, based on the total weight of the silicon-carbon material and the second carbon-based particles, the weight content of the silicon-carbon material is ≤20wt%, and the total weight of the second carbon-based particles is ≥80wt%.
[0073] In one example, in the first negative electrode active material layer, based on the total weight of the silicon-oxygen material and the first carbon-based particles, the weight content of the silicon-oxygen material is ≤20wt%, and the total weight of the first carbon-based particles is ≥80wt%, and in the second negative electrode active material layer, based on the total weight of the silicon-carbon material and the second carbon-based particles, the weight content of the silicon-carbon material is ≤20wt%, and the total weight of the second carbon-based particles is ≥80wt%, and the median particle size Dv50 of the first carbon-based particles is 10μm-20μm, and the median particle size Dv50 of the first carbon-based particles is 10μm-20μm. At this time, the silicon-oxygen material in the first negative electrode active material layer and the silicon-carbon material in the second negative electrode active material layer can provide a higher specific capacity, thereby improving the energy density of the battery, and by controlling the contents of the silicon-oxygen material, the silicon-carbon material, the first carbon-based particles and the second carbon-based particles, the battery's cycle expansion will not be too large due to excessive silicon doping, affecting the cycle performance; at the same time, the average particle size of the first carbon-based particles and the average particle size of the second carbon-based particles are controlled to improve the kinetic properties of the negative electrode sheet, thereby improving the cycle performance of the battery.
[0074] In one example, the first carbon-based particles include natural graphite and / or artificial graphite.
[0075] In one example, the second carbon-based particles include natural graphite and / or artificial graphite.
[0076] In one example, the surface density of the first negative electrode active material layer is 1 mg / cm 2 -10mg / cm 2 (For example, 1 mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 or 10mg / cm 2 ).
[0077] In one example, the porosity of the first negative active material layer is 30%-45% (eg, 30%, 32%, 35%, 38%, 40%, 42% or 45%).
[0078] In one example, the surface density of the second negative electrode active material layer is 0.5 mg / cm 2 -6mg / cm 2 (For example, 0.5 mg / cm 2 , 1mg / cm 2, 1.5mg / cm 2 , 2mg / cm 2 , 2.5mg / cm 2 、3mg / cm 2 、3.5mg / cm 2 , 4mg / cm 2 , 4.5mg / cm 2 , 5mg / cm 2 , 5.5mg / cm 2 or 6mg / cm 2 ).
[0079] In one example, the porosity of the second negative active material layer is 25%-40% (eg, 25%, 28%, 30%, 32%, 35%, 38% or 40%).
[0080] In one example, the surface density of the first negative electrode active material layer is 1 mg / cm 2 -10mg / cm 2 , and the surface density of the second negative electrode active material layer is 0.5 mg / cm 2 -6mg / cm 2 . Controlling the surface density of the first negative electrode active material layer and the surface density of the second negative electrode active material layer can take into account both energy density and fast charging performance. At this time, the negative electrode sheet will not increase polarization and deteriorate fast charging capability due to surface density, nor will it cause insufficient energy density due to too low surface density; at the same time, the surface density of the first negative electrode active material layer is appropriately higher than the surface density of the second negative electrode active material layer, so that the silicon oxide material in the first negative electrode active material layer can accommodate as many lithium ions as possible during the fast charging process and conduct them to the second negative electrode active material layer, so that the battery has the advantages of high energy density and good fast charging performance.
[0081] In one example, the compaction density of the negative electrode sheet is 1.5 g / cm 3 -1.7g / cm 3 (For example, 1.5 g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 or 1.7 g / cm 3 ). The compaction density of the negative electrode sheet is the overall compaction density of the negative electrode sheet.
[0082] In one example, the porosity of the first negative electrode active material layer is 30%-45%, the porosity of the second negative electrode active material layer is 25%-40%, and the compaction density of the negative electrode sheet is 1.5 g / cm 3 -1.7g / cm 3The relatively high porosity of the first negative electrode active material layer can promote the electrolyte to infiltrate the inside of the electrode, which is beneficial to the rapid transmission of lithium ions. The relatively slightly lower porosity of the second negative electrode active material layer can improve the space utilization, reduce the overall thickness of the negative electrode, and improve the energy density of the battery. At the same time, the compaction density of the negative electrode sheet is controlled within the above range to ensure close contact between the particles of silicon-oxygen material and carbon-based material, as well as close contact between the particles of silicon-carbon material and carbon-based material, thereby forming an effectively cross-linked conductive network and improving the fast charging performance of the battery. At this time, the electrolyte will not infiltrate the inside of the negative electrode sheet poorly due to the excessively high compaction density of the negative electrode sheet, hindering the transmission of lithium ions and reducing the fast charging performance of the battery.
[0083] In one example, the negative electrode current collector includes a metal layer and a primer layer located on at least one side of the metal layer, and the thickness of the primer layer is 0.5 μm-2 μm. When the negative electrode current collector includes a primer layer, the peel strength between the second negative electrode active material layer and the negative electrode current collector can be effectively improved, and the bonding effect between the second negative electrode active material layer and the negative electrode current collector can be enhanced, thereby improving the cycle performance of the battery. The present invention does not limit the specific components of the primer layer, and the primer layer conventionally used in the art can be selected. For example, the primer layer can include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), conductive carbon black, graphene, and carbon nanotubes.
[0084] In one example, the metal layer includes copper foil.
[0085] In one example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on both side surfaces of the negative electrode current collector; the negative electrode active material layer includes a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer is away from the negative electrode current collector, and the second negative electrode active material layer is close to the negative electrode current collector.
[0086] In one example, the first negative electrode active material layer further includes a first binder, and the second negative electrode active material layer further includes a second binder.
[0087] In one example, the first binder includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid, polyacrylic acid salt, polyvinyl alcohol, polyacrylonitrile, polyacrylamide, polymethacrylate, alginic acid, alginate, polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0088] In one example, the second binder includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid, polyacrylic acid salt, polyvinyl alcohol, polyacrylonitrile, polyacrylamide, polymethacrylate, alginic acid, alginate, polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0089] In one example, the first binder and the second binder are the same or different.
[0090] In one example, the first binder and the second binder both include styrene-butadiene rubber. When the first binder and the second binder both include styrene-butadiene rubber, the compatibility between the slurry of the first negative electrode active material layer and the slurry of the second negative electrode active material layer is optimal during coating, and the two layers of slurry will not shrink at the edges due to poor compatibility during coating, nor will the upper and lower layers be mixed, and after baking, the first negative electrode active material layer and the second negative electrode active material layer will not be peeled off.
[0091] In one example, the first negative electrode active material layer includes a first negative electrode active material, and the first negative electrode active material includes a silicon-oxygen material and first carbon-based particles.
[0092] In one example, the first negative electrode active material layer further includes a first conductive agent and a first thickener.
[0093] In one example, the first conductive agent includes one or more of conductive carbon black (SP), Ketjen black, acetylene black, graphite conductive agent (KS-6, KS-15, SO, SEG-6), carbon fiber (VGCG), carbon nanotube (CNT) and graphene.
[0094] In one example, the first thickener includes one or more of carboxymethyl cellulose (CMC), lithium carboxymethyl cellulose (CMCLi) and sodium carboxymethyl cellulose (CMCNa).
[0095] In one example, based on the total weight of the first negative electrode active material layer, the weight content of the first negative electrode active material is 93%-99.7% (for example, 93%, 94%, 95%, 96%, 97%, 98% or 99.7%), the weight content of the first conductive agent is 0.1%-1% (for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%), the weight content of the first binder is 0.1%-3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%), and the first thickener is 0.1%-3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%).
[0096] In one example, based on the total weight of the first negative electrode active material, the weight content of the silicon oxide material is 0.1%-20% (for example, 0.1%, 0.5%, 1%, 5%, 10%, 15% or 20%), and the weight content of the first carbon-based particles is 99.9%-80% (for example, 99.9%, 99.5%, 99%, 95%, 90%, 85% or 80%).
[0097] In one example, the second negative electrode active material layer includes a second negative electrode active material, and the second negative electrode active material includes a silicon-carbon material and second carbon-based particles.
[0098] In one example, the second negative electrode active material layer further includes a second conductive agent and a second thickener.
[0099] In one example, the second conductive agent includes one or more of conductive carbon black (SP), Ketjen black, acetylene black, graphite conductive agent (KS-6, KS-15, SO, SEG-6), carbon fiber (VGCG), carbon nanotube (CNT) and graphene.
[0100] The first conductive agent and the second conductive agent may be the same or different.
[0101] The first thickener and the second thickener may be the same or different.
[0102] In one example, the second thickener includes one or more of carboxymethyl cellulose (CMC), carboxymethyl cellulose lithium (CMCLi) and carboxymethyl cellulose sodium (CMCNa).
[0103] In one example, based on the total weight of the second negative electrode active material layer, the weight content of the second negative electrode active material is 93%-99.7% (for example, 93%, 94%, 95%, 96%, 97%, 98% or 99.7%), the weight content of the second conductive agent is 0.1%-1% (for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%), the weight content of the second binder is 0.1%-3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%), and the second thickener is 0.1%-3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%).
[0104] In one example, based on the total weight of the second negative electrode active material, the weight content of the silicon-carbon material is 0.1%-20% (for example, 0.1%, 0.5%, 1%, 5%, 10%, 15% or 20%), and the weight content of the second carbon-based particles is 99.9%-80% (for example, 99.9%, 99.5%, 99%, 95%, 90%, 85% or 80%).
[0105] The second aspect of the present invention provides a lithium-ion secondary battery, which may include the negative electrode sheet described in the first aspect of the present invention.
[0106] For the materials of the battery other than the negative electrode sheet, they can all be carried out in the manner of the art, and all can achieve the effect of兼顾较好的首次库伦效率和循环稳定性,并且具有较低的循环膨胀率的效果. (It is recommended to provide a more accurate translation for this sentence as the current description is a bit unclear. For example, "兼顾较好的首次库伦效率和循环稳定性,并且具有较低的循环膨胀率的效果" could be translated more precisely as "achieving a good balance between the initial Coulombic efficiency and cycle stability while having a low cycle expansion rate".)
[0107] In one example, the lithium-ion secondary battery further includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a substance with the chemical formula LiaNi x Co y Mn z A k O2, where 0.9 ≤ a ≤ 1.1 (for example, 0.9, 0.95, 1, 1.05 or 1.1), 0.8 ≤ x ≤ 0.95 (for example, 0.8, 0.85, 0.9 or 0.95), 0 < y ≤ 0.2 (for example, 0.01, 0.05, 0.1, 0.15 or 0.2), 0 < z ≤ 0.2 (for example, 0.01, 0.05, 0.1, 0.15 or 0.2), 0 ≤ k ≤ 0.05 (for example, 0, 0.01, 0.02, 0.03, 0.04 or 0.05), and A is selected from at least one of Al, Zr, B, Y, Sr, W, Ti and Nb. When the positive electrode active material satisfies the above conditions, the positive electrode sheet has a high specific capacity, which is beneficial to improving the energy density of the battery.
[0108] Among them, A is a doping element, and when k is 0, it means that the positive electrode active material does not include the doping element A.
[0109] In one example, 0.9 ≤ x ≤ 0.95.
[0110] In one example, the positive electrode active material has a layered structure.
[0111] In one example, the positive electrode active material includes a substance with the chemical formula Li a Ni x Co y Mn z A kA substance of O2, 0.9 ≤ a ≤ 1.1, 0.8 ≤ x ≤ 0.95, 0 < y ≤ 0.2, 0 < z ≤ 0.2, 0 ≤ k ≤ 0.05, and the positive electrode active material has a layered structure.
[0112] In one example, the positive electrode active material includes single crystal particles and polycrystalline particles, and the mass ratio of the polycrystalline particles to the single crystal particles is 2.33 - 4 (for example, 2.33, 2.5, 3, 3.5 or 4). At this time, the positive electrode active material is used by mixing single crystal particles with polycrystalline particles, and mainly with polycrystalline particles, which can make the positive electrode sheet have good cycle and rate performance, and will not cause insufficient high-rate and charge-discharge performance of the battery due to excessive single crystal particles, nor will it cause excessive side reactions at the interface of the positive electrode sheet due to excessive polycrystalline particles, affecting the battery cycle performance.
[0113] In one example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, a positive electrode conductive agent, and a positive electrode binder.
[0114] In one example, the positive electrode conductive agent includes at least one of conductive carbon black (SP), Ketjen black, acetylene black, graphite conductive agent (KS-6, KS-15, S-O, SEG-6), carbon fiber (VGCG), carbon nanotube (CNT), and graphene.
[0115] In one example, the positive electrode binder includes one or more of PVDF, PVDF-HFP, polytetrafluoroethylene, polyacrylonitrile, polyimide, and perfluorosulfonic acid ionomer binder.
[0116] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 92% - 98% (for example, 92%, 93%, 94%, 95%, 96%, 97% or 98%), the weight content of the positive electrode conductive agent is 1% - 4% (for example, 1%, 2%, 3% or 4%), and the weight content of the positive electrode binder is 1% - 4% (for example, 1%, 2%, 3% or 4%).
[0117] In one example, the CB value of the lithium-ion secondary battery is 1.1 - 1.2 (for example, 1.1, 1.12, 1.15, 1.18 or 1.2). The CB value is the ratio of the theoretical capacity of the battery negative electrode to the theoretical capacity of the positive electrode. Controlling the CB value within the above range, the battery will not have insufficient fast charging ability due to too low CB value, nor will it have low battery energy density due to too high CB value.
[0118] The negative electrode sheet and the positive electrode sheet in the lithium-ion secondary battery can be combined together by winding or laminating.
[0119] In one example, the lithium-ion secondary battery includes a hard outer shell, which is beneficial to suppress the expansion of silicon-oxygen materials and silicon-carbon materials and reduce the expansion rate of the battery.
[0120] In one example, the hard shell is square.
[0121] In one example, the cut-off voltage of the lithium-ion secondary battery is ≤4.25V, and at this time, the battery can achieve better fast charging performance at high voltage.
[0122] In one example, the lithium-ion secondary battery includes an electrolyte.
[0123] In one example, the electrolyte includes a lithium salt and an organic solvent, and the lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF4), lithium difluorobis(oxalatoborate) (LiDFOP) and lithium bis(trifluoromethylsulfonyl)imide.
[0124] In one example, the organic solvent includes one or more of ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), ethyl methyl carbonate (EMC), dimethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, diethyl carbonate (DMC), ethyl formate, ethyl acetate (EA), ethyl propionate (EP) and propyl propionate (PP).
[0125] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 10%-15% (e.g., 10%, 11%, 12%, 13%, 14% or 15%), and the weight content of the organic solvent is 85%-90% (e.g., 85%, 86%, 87%, 88%, 89% or 90%).
[0126] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0127] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0128] The following examples are used to illustrate the negative electrode sheet and lithium ion secondary battery of the present invention.
[0129] Example 1
[0130] The lithium ion secondary battery was prepared as follows:
[0131] (1) Preparation of negative electrode
[0132] Component preparation: First negative electrode active material layer: 95 parts by weight of first negative electrode active material (13 parts by weight of silicon oxide material, 87 parts by weight of first carbon-based material (graphite)), 0.5 parts by weight of first conductive agent (conductive carbon black), 2.5 parts by weight of first binder (SBR), 2 parts by weight of first thickener (carboxymethyl cellulose lithium (CMCLi));
[0133] Second negative electrode active material layer: 95 parts by weight of second negative electrode active material (11 parts by weight of silicon-carbon material, 89 parts by weight of second carbon-based material (graphite)), 0.5 parts by weight of second conductive agent (conductive carbon black), 2.5 parts by weight of second binder (SBR), and 2 parts by weight of second thickener (carboxymethyl cellulose lithium (CMCLi)).
[0134] Preparation: a first negative electrode active material, a first thickener, a first binder and a first conductive agent are mixed, and a uniformly dispersed mixture is obtained by high-speed stirring, and water is used as a solvent to prepare a slurry of the first negative electrode active material layer, wherein the solid content in the slurry is 50wt%;
[0135] The second negative electrode active material, the second thickener, the second binder and the second conductive agent are mixed, stirred at high speed to obtain a uniformly dispersed mixture, and water is used as a solvent to prepare a slurry of the second negative electrode active material layer, wherein the solid content in the slurry is 50 wt %.
[0136] During coating, the first negative electrode active material layer and the second negative electrode active material layer slurry should be placed in the upper and lower pipes of the double-layer extrusion coater respectively, and sprayed evenly on one side of the negative electrode current collector copper foil to form two wet films, where the surface density of the first negative electrode active material layer and the second negative electrode active material layer are 4.5 mg / cm 2 and 3.5 mg / cm 2 Then, after baking, a single-sided negative electrode is obtained. The other side is coated in the same way to form a double-sided negative electrode. After baking and rolling, a negative electrode sheet is obtained. Among them, the porosity of the first negative electrode active material layer is 36%, and the porosity of the second negative electrode active material layer is 32%.
[0137] (2) Preparation of positive electrode
[0138] Component preparation: Positive electrode active material: LiNi 0.92 Co 0.02 Mn 0.04 Al 0.02 O2, 97 parts by weight, positive electrode binder: PVDF, 1.5 parts by weight, positive electrode conductor: conductive carbon black, 1.5 parts by weight;
[0139] The positive electrode active material, positive electrode binder and positive electrode conductive agent are mixed, stirred at high speed to obtain a uniformly dispersed mixture, and NMP is used as a solvent to prepare a positive electrode active material slurry with a solid content of 70wt%. The slurry is evenly coated on both sides of the positive electrode current collector, dried, and rolled to obtain a positive electrode sheet.
[0140] (3) Preparation of electrolyte
[0141] Lithium salt: LiPF6, 10 parts by weight;
[0142] Organic solvent: ethylene carbonate, 45 parts by weight, diethyl carbonate, 40 parts by weight, FEC, 5 parts by weight.
[0143] In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), the organic solvents are mixed evenly, and then fully dried lithium salts are quickly added thereto to obtain the desired electrolyte.
[0144] (4) Diaphragm
[0145] The diaphragm substrate is 9μm, the single-sided ceramic is 2μm, and the double-sided glue layer is 1μm on each side. The glue is oil-based coating.
[0146] (5) Preparation of lithium-ion batteries
[0147] The positive electrode sheet of step (1), the negative electrode sheet of step (2) and the separator of step (4) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step (3) is injected into the outer packaging, and a lithium ion battery is obtained after vacuum packaging, standing, forming, shaping, sorting and other processes. The CB value of the lithium ion battery is 1.12. See Table 1-1 and Table 1-2 for details.
[0148] Example 2
[0149] Refer to Example 1 to adjust the performance parameters of the negative electrode sheet, with specific reference to Table 1-1 and Table 1-2.
[0150] Example 3
[0151] The same method is carried out as in Example 1, except that the performance parameters of the negative electrode sheet are adjusted. For details, see Table 1-1 and Table 1-2.
[0152] Example 4 Group
[0153] This example group is carried out with reference to Example 1, except that m1 / m2 or the mass content of element Mg in the silicon-oxygen material is changed, as shown in Table 1-1 and Table 1-2 for details.
[0154] Example 5 Group
[0155] This embodiment group is carried out with reference to embodiment 1, except that D2 / D1 and / or D4 / D3 are changed, see Table 1-1 and Table 1-2 for details.
[0156] Example 6 Group
[0157] This example group was carried out with reference to Example 1, except that the chemical formula of the positive electrode active material was changed, as shown in Table 1-1 and Table 1-2 for details.
[0158] Example 7 Group
[0159] This embodiment group is carried out with reference to the embodiment 1, except that d1 and d3 are changed by adjusting the surface density of the first negative electrode active material layer, as shown in Table 1-1 and Table 1-2 for details.
[0160] Example 8 Group
[0161] This embodiment group is carried out with reference to the embodiment 1, except that d2 and d4 are changed by adjusting the surface density of the second negative electrode active material layer, as shown in Table 1-1 and Table 1-2 for details.
[0162] Example 9
[0163] The same method is carried out as in Example 1, except that no primer layer is present in the negative electrode current collector. For details, see Table 1-1 and Table 1-2.
[0164] Example 10 Group
[0165] This embodiment group is carried out with reference to the embodiment 1, except that the thickness of the carbon layer on the surface of the silicon-oxygen material is changed, as shown in Table 1-1 and Table 1-2 for details.
[0166] Comparative Example 1
[0167] The same procedure is carried out as in Example 1, except that graphite, silicon-carbon material and silicon-oxygen material are mixed together and coated in a single layer.
[0168] Comparative Example 2
[0169] The process is carried out in accordance with Example 1, except that the silicon-oxygen ratio m2 in the silicon-carbon material is changed so that m1>m2. For details, see Table 1-1 and Table 1-2.
[0170] Table 1-1
[0171]
[0172]
[0173]
[0174] *Same as Example 1.
[0175] Table 1-2
[0176]
[0177]
[0178]
[0179] *Same as Example 1.
[0180] Test Case
[0181] The lithium ion secondary batteries obtained in the examples and comparative examples were tested as follows:
[0182] 1. Normal temperature cycle test
[0183] At 25°C, in the charge and discharge window of 4.2V to 2.5V, 1C / 1C charge and discharge cycle was performed. The test process was as follows: first, 1C constant current charging to 4.2V, then constant voltage charging, cut-off current 0.05C, and finally 1C constant current discharge to 2.5V, and the test was repeated in this way. The number of times when the ratio of discharge capacity to the first discharge capacity (capacity retention rate) reached 80% was recorded in Table 2.
[0184] The ratio of the thickness of the battery at 50% SOC at the end of the cycle to the thickness in the initial state is recorded, which is the cycle expansion rate of the battery cell.
[0185] The ratio of the DCR value of the battery at 50% SOC at the end of the cycle to the DCR value in the initial state is recorded, which is the DCR growth rate.
[0186] 2. Fast charging window test
[0187] At room temperature, charge the battery cell nC (n=1, 2, 3, 4, 5) to 4.2V and then charge at a constant voltage with a cut-off current of 0.05C and let stand for 30min; discharge at 1C to 2.5V and let stand for 30min; repeat the charge and discharge cycle 20 times, and finally end the test after the battery cell is fully charged (100% SOC) and dissect it to observe whether lithium deposition occurs on the negative electrode side.
[0188] Record the maximum rate at which the battery does not release lithium, which is the fast charging window of the battery.
[0189] During the cyclic charge and discharge process, the temperature change of the battery during the charging process is recorded, and the maximum value is the maximum temperature rise of the battery.
[0190] 3. Energy density test
[0191] At 25°C, the battery is charged at 0.33C constant current and constant voltage to the upper limit voltage (4.2V), and then discharged at 0.33C to the lower limit voltage (2.5V). At this time, the energy released by the battery can be measured; the calculation method of battery weight energy density (WED) is: WED = energy / battery weight.
[0192] The obtained results are recorded in Table 2.
[0193] Table 2
[0194]
[0195] It can be seen from Table 2 that the battery prepared by the negative electrode sheet of the present invention has a longer cycle number, a higher fast charging window, a lower maximum temperature rise and a higher energy density than the comparative example. The battery including the negative electrode sheet of the present invention can take into account high energy density, fast charging capability and better cycle stability.
[0196] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer is away from the negative electrode current collector, and the second negative electrode active material layer is close to the negative electrode current collector; The first negative electrode active material layer includes a silicon-oxygen material, the silicon-oxygen material includes the element Si and the element O, and in the silicon-oxygen material, the mass ratio of the element Si to the element O is m1; the second negative electrode active material layer includes a silicon-carbon material, the silicon-carbon material includes the element Si, the element C and the element O, and in the silicon-carbon material, the mass ratio of the element Si to the element O is m2; m1 <m2。 2. The negative electrode sheet according to claim 1, wherein: m1 / m2 is 0.001-0.12; preferably m1 / m2 is 0.0023-0.05; and / or, m1 is 0.8-1.2; preferably 0.9-1; And / or, m2 is 7.5-500; preferably 20-44.
3. The negative electrode sheet according to claim 1 or 2, wherein: When the battery including the negative electrode sheet is in a 0% SOC state, the vertical distance from the surface of the silicon-oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d1, and the vertical distance from the surface of the silicon-carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d2; d1 is 0μm-35μm, and d2 is 0μm-26μm; preferably, d1 is 0μm-30μm, and d2 is 0μm-20μm; And / or, when the battery including the negative electrode sheet is in a 100% SOC state, the vertical distance from the surface of the silicon-oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d3, and the vertical distance from the surface of the silicon-carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d4; d3 is 0μm-40μm, and d4 is 0μm-35μm; preferably, d3 is 0μm-36μm, and d4 is 0μm-30μm.
4. The negative electrode sheet according to claim 1 or 2, wherein: In the silicon-oxygen material, the mass ratio of element Si to element O is 0.8-1.2; And / or, in the silicon-carbon material, the mass ratio of element Si to element C is 0.6-1.5; preferably 0.9-1.1; And / or, the silicon-oxygen material further includes element Li and / or element Mg; Preferably, the mass content of element Mg in the silicon-oxygen material is 200 ppm-10000 ppm.
5. The negative electrode sheet according to claim 4, wherein: The first negative electrode active material layer further includes first carbon-based particles, and the second negative electrode active material layer further includes second carbon-based particles; The average particle size of the silicon-oxygen material is D1, the average particle size of the first carbon-based particles is D2, the average particle size of the silicon-carbon material is D3, and the average particle size of the second carbon-based particles is D4. D1, D2, D3 and D4 satisfy: D2 / D1 is 1.1-2.3, and D4 / D3 is 1.3-2.6; Preferably, D2 / D1 is 1.5-2, and D4 / D3 is 1.6-2.
2.
6. The negative electrode sheet according to claim 5, wherein: D1 is 5μm-15μm; and / or, D2 is 4 μm-22 μm; and / or, D3 is 6 μm-14 μm; And / or, D4 is 8μm-25μm.
7. The negative electrode sheet according to claim 1 or 2, wherein: The first negative electrode active material layer further includes first carbon-based particles, and the second negative electrode active material layer further includes second carbon-based particles; The silicon-oxygen material is located in the gaps formed by the first carbon-based particles; And / or, the silicon-carbon material is located in gaps formed by a plurality of the second carbon-based particles.
8. The negative electrode sheet according to claim 1 or 2, wherein: The surface density of the first negative electrode active material layer is 1 mg / cm 2 -10mg / cm 2 , the porosity of the first negative electrode active material layer is 30%-45%; And / or, the surface density of the second negative electrode active material layer is 0.5 mg / cm 2 -6mg / cm 2 , the porosity of the second negative electrode active material layer is 25%-40%; And / or, the negative electrode current collector comprises a metal layer and a conductive layer located on both sides of the metal layer, and the thickness of the conductive layer is 0.5 μm-2 μm; And / or, the first negative electrode active material layer further includes a first binder, and the second negative electrode active material layer further includes a second binder; preferably, the first binder and the second binder both include styrene-butadiene rubber.
9. A lithium ion secondary battery, characterized in that: The lithium ion secondary battery comprises the negative electrode sheet according to any one of claims 1 to 8.
10. The lithium ion secondary battery according to claim 9, wherein The lithium ion secondary battery further includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a substance with the chemical formula Li a Ni x Co y Mn z A k O2, where 0.9 ≤ a ≤ 1.2, 0.8 ≤ x ≤ 0.95, 0 < y ≤ 0.2, 0 < z ≤ 0.2, 0 ≤ k ≤ 0.05, and A is selected from at least one of Al, Zr, B, Y, Sr, W, Mg, Fe, Ti, and Nb; Preferably, the positive electrode active material has a layered structure.